360-Degree Evaluation of Educational Skills of Senior Nursing Students: A Retrospective Study - Yusuf Türköz; Cemre Paylan Akkoç; Gülsüm Çonoğlu; Nilay Özkütük; Fatma Orgun (Journal of Nursology)
Objective: To assess the educational skills of senior nursing students using the 360-degree evaluation method.Methods: This study retrospectively analyzed the scores of senior nursing students (n = 205) in terms of their educational skill evaluation by the instructor, preceptor, self, and peers. Data were collected retrospectively from the archived student files of the course between August 2022 and October 2022. SPSS for Windows v. 22.0 was used for statistical analysis. P<.05 was accepted as the statistical significance level.Results: Of the students, 90.7% (n=186) were female, and 9.3% (n=19) were male. The mean and standard deviation scores on the education skills evaluation form were found to be 92.88 ± 7.65 for instructor evaluation, 94.67±7.56 for preceptor evaluation, 96.38±10.23 for self- evaluation, and 97.57±8.60 for peer-evaluation. There was a positive and weakly significant correlation between instructor and preceptor evaluations (r=.352; P<.001), but instructor evaluation did not have a significant correlation with self-evaluation or peer-evaluation (P>.05). A positive and moderately significant correlation was observed between self-evaluation and peer-evaluation (r=.634; P<.001).Conclusion: The students tend to give higher scores in self-evaluation and peer-evaluation. Therefore, it is recommended that evaluators adhere to established rules and undergo proper training to prevent a lack of agreement in evaluation among raters and ensure a consistent assessment.